Civil Servant Performance Appraisal Through Electronic Performance System (E-Kinerja) at the Regional Revenue and Financial Management Agency of Tomohon City - Thelma Wawointana; Selpius Kandou; Injilia T. Ngantung; Patriani Supit; Hendrasari B. R. Rawung (Technium Social Sciences Journal, 2024)
This research describes employee performance assessment through the e-performance system at the Tomohon City Regional Financial and Revenue Management Agency. This research uses a qualitative approach by collecting data using Observation, Interview and Documentation techniques, the data obtained is analyzed descriptively qualitatively. The results of this research show that: 1. Indicators of the mechanism for implementing the e-kinerja system there are still a number of technical problems such as difficulty logging in and inadequate wifi coverage. Network disruptions or power outages that require employees to return to manual charging methods. And there is a lack of special training for employees. This is of course very influential in the employee performance appraisal process so that it can be effective and efficient in its implementation. 2. The objective indicators for e-kinerja assessment still experience obstacles such as a lack of understanding of the indicators that must be achieved in e-kinerja, a lack of supervision and warnings, a lack of ASN discipline when filling out e-kinerja.